Study of the variability of scapular inclination and the glenoid version - considerations for preoperative planning: clinical-radiological study - Fulin, Petr; Kysilko, Martin; Pokorny, David; Padr, Radek; Kasprikova, Nikola; Landor, Ivan; Sosna, Antonin (BMC musculoskeletal disorders, 2017)
BACKGROUND: Preoperative planning with the aid of imaging methods is a principal factor in successful surgery on the shoulder. This work aims to evaluate the variability of glenoid version, spiralling twist and scapular inclination in relation to the frontal axis. Studies focusing on measuring the variability of scapular inclination in the standardised rest position are lacking in the literature. METHODS: We evaluated 104 CT scans of the shoulder. We measured the glenoid version with respect to the scapular axis at three levels. We measured the scapular inclination angle in relation to the sagittal plane and we determined scapular inclination in relation to the frontal axis. Statistical evaluation was performed using the marginal linear model and parameters were estimated using the generalised least squares method, which enables the dependency of measurements performed on the same subject to be taken into consideration. RESULTS: The highest values of retroversion are attained by the glenoid in the cranial section (average -9.96°, range -29.7 to +13.2°). Proof of the spiralling twist is the decline in retroversion at the centre of the glenoid (average -2.09°, range -16.7 to +11.6°). Retroversion decreases further in the inferior direction (average -0.5°, range -20.9 to +17.5°). The average thoracoscapular angle is 45.46°, ranging from 13.1 to 69.0°. The average scapular inclination in relation to the frontal plane is 44.54°, ranging from 21.0 to76.9°. CONCLUSIONS: During preoperative planning, the surgeon should take into consideration not only the glenoid version in relation to the scapular axis, but also the value of the scapular inclination so as to eliminate possible surgical errors, optimise prosthesis implantation and thus decrease the risk of functional restrictions of the joint. CLINICAL TRIAL REGISTRATION: Ethics Committee for Multi-Centric Clinical Trials (EK-554/14,29thApril 2014).
Keywords: Young Adult; Male; Shoulder Joint; počítačová rentgenová tomografie; Scapula; mladý dospělý; Inclination; lopatka; Version; Adult; Glenoid; Aged; dospělí; mužské pohlaví; senioři; anatomická variace; Tomography, X-Ray Computed; předoperační péče; senioři nad 80 let; lidé; ženské pohlaví; ramenní kloub; Humans; Anatomic Variation; Aged, 80 and over; Angle; Female; Preoperative Care; lidé středního věku; Arthroplasty; Middle Aged; Preoperative planning